2001
DOI: 10.1159/000055404
|View full text |Cite
|
Sign up to set email alerts
|

HER2 as a Prognostic Factor in Breast Cancer

Abstract: HER2 amplification/overexpression is a marker of poor prognosis in breast cancer. The prognostic impact of HER2 positivity is lower in node-negative compared with node-positive women. The only significant, independent prognostic factors in breast cancer are node status, HER2 status and menopausal status. HER2-positive tumors also contain p53 abnormalities, tend to be hormone receptor and bcl-2 negative, have lymphoid infiltration (LI) and a high mitotic index. Patients with LI who are HER2 positive have a bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
131
1
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(149 citation statements)
references
References 18 publications
10
131
1
7
Order By: Relevance
“…Despite the total lack of methodologic standardization, the prevalence of HER-2-positive tumors is reasonably constant among studies, ranging from 19% to 35% (Table 2). This is in line with the reported proportion of HER-2-positive tumors in different settings (29).…”
Section: Resultssupporting
confidence: 90%
“…Despite the total lack of methodologic standardization, the prevalence of HER-2-positive tumors is reasonably constant among studies, ranging from 19% to 35% (Table 2). This is in line with the reported proportion of HER-2-positive tumors in different settings (29).…”
Section: Resultssupporting
confidence: 90%
“…It is involved in normal breast growth and development, and overexpression of HER2 seems to play a role in malignant transformation and tumourigenesis. HER2 was first reported in preinvasive breast cancer, and higher expression in DCIS than in IDC has been demonstrated (Ross and Fletcher, 1998;Menard et al, 2001). The explanation of this phenomenon was, that HER2-negative IDCs might not derive from DCIS, but develop from another lesion, the atypical ductal hyperplasia (ADH), which showed no HER2 amplification (Menard et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…HER2 was first reported in preinvasive breast cancer, and higher expression in DCIS than in IDC has been demonstrated (Ross and Fletcher, 1998;Menard et al, 2001). The explanation of this phenomenon was, that HER2-negative IDCs might not derive from DCIS, but develop from another lesion, the atypical ductal hyperplasia (ADH), which showed no HER2 amplification (Menard et al, 2001). The same might be the case in PRL-3 expression, but to date, there is no data on the expression of PRL-3 in ADH.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical studies have evaluated the relationship between HER2 and breast cancer outcome, and most have shown that women with HER2-positive tumors have a poorer prognosis than women with HER2-negative tumors (Me´nard et al, 2000(Me´nard et al, , 2001bMasood and Bui, 2002). However, while the prognostic value of HER2 amplification/overexpression in node-positive patients has been widely demonstrated, there is no consensus on its value in node-negative cases (Press et al, 1997;Ross et al, 1998;Volpi et al, 2000;Cooke et al, 2001).…”
Section: Her2 Status In Prognosis and Prediction Of Response To Therapymentioning
confidence: 99%